PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER DAN MODEL TALKING STICK TERHADAP MOTIVASI DAN HASIL BELAJAR IPS - Nur Syahru Ramadhan; Muhammad Nawir; Nur Salam (Jurnal Penelitian dan Pendidikan IPS, 2024)
This research aims to determine the differences in the influence of the Numbered Heads Together (NHT) and Talking Stick learning models on student motivation and learning outcomes. The research design used in this experimental research is Factorial Design Experiment, using Pretest-Posttest, Nonequivalent Multiple Group Design. This research uses two experimental classes. The first experimental class (X1) was treated using the NHT model and the second experimental class (X2) was treated using the Talking Stick model with a total of 50 students. The instruments used in this research were test sheets, invitation sheets, and documentation. The data analysis techniques used were descriptive tests and inferential tests (normality, homogeneity and Manova tests). Based on the results of data analysis carried out using SPSS 25, there is no significant influence between the simultaneous learning model on the motivation and social studies learning outcomes of fifth grade students at SDN Kaluku Bodoa with a significant value of 0.822> 0.05, which means that H1 is rejected. H0 is accepted.